Cutaneous Manifestations of Breast Cancer Patients in Combination with Capecitabine and Lapatinib Chemotherapy - Nita Damayanti Sulistianingrum; Niken Indrastuti; Yohanes Widodo Wirohadidjojo (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
The combination of chemotherapy with lapatinib and capecitabine in human epidermal growth factor receptor 2 (HER2) positive breast cancer is quite effective. The combination of these two agents increases the risk of dermatological toxicities. A woman, 38 years old, HER2 positive breast cancer with a combination of chemotherapy agents between lapatinib and capecitabine gives an overview of skin toxicities such as acneiform eruptions, palmar-plantar erythrodysesthesia (PPE), and paronychia. Therapy, in this case, aims at clinical improvement. The combination of lapatinib and capecitabine has a side effect profile like each drug. Combined use of the two agents increases the incidence of skin side effects, including acneiform eruptions, PPE, and paronychia, compared to monotherapy. Early awareness of the side effects of chemotherapeutic agents is needed for early treatment to prevent the worsening of the condition and discontinuation of chemotherapeutic agents due to drug side effects.